Tourism, diasporas, and space - Coles, Tim; Timothy, Dallen J. (Routledge studies in contemporary geographies of leisure, tourism, and mobility, 2004)
The book introduces the main features and constructs of diasporas, and explores their implications for the consumption, production and practices of tourism.